The effect of cooking method on proximate composition, total iron, heme iron and non-heme iron in haruan (channa sp.), catfish ( clariassp,), siakap (lates CALCARIFER) and tilapia (Oreochromis sp.) - Anuar, Siti Nadia (Universiti Sains Malaysia, 2015)
Nowadays, the freshwater fish industry has increased in line with the increased demand from the consumer due to its richness nutrient especially protein, mineral and vitamin. In Malaysia, fish are rarely eaten raw and mostly will be cooked with various types of cooking method but this process are involves thermal treatment which will affect the nutrient content in fish especially iron. However, studies on the effect of cooking method on total iron, heme iron and non-heme iron in fish specifically in freshwater fish was limited. So the aim of this study was to determine the effect of difference cooking method on proximate composition, total iron, heme iron and non-heme iron in Haruan (Charina sp), Catfish (Clarias sp), Siakap (Lates calcarifer) and Tilapia (Oreochromis sp). The samples was bought at Pasar Siti Khadijah and each types of freshwater fish was divided in five group that are raw, fried, baked, boiled and steamed method. The proximate composition (moisture, ash, lipid and protein), total iron, heme and non-heme iron composition was studied. Iron (II) standard graph was used to determine the value of total iron and heme iron in all samples. The amount of non-heme iron was obtained through differences between total iron and heme iron. Effect of cooking method on proximate composition was significantly different especially in fried method; where it causes a significant decreased of moisture especially in Tilapia (67.8 %). At the same time, fried method increased the ash, protein and lipid content in all species except for catfish. Meanwhile the steamed method showed the significant increase in moisture, lipid and protein in certain type of fish. All sample showed a significant different on the amount of total iron between fresh and cooked sample. The amount of heme iron in Haruan and Tilapia showed a significant different while catfish and Siakap are otherwise. However the effects of cooking method on the amount of heme iron are different in Haruan and Tilapia. Then the values of non-heme iron in all samples are significant at p<0.05. Briefly, the changes of nutrient due to cooking method are also depends on the type of fish.